(untitled) (Nóema, 2022)
This article explores the birth of American Phenomenology in Josiah Royce’s “New Phenomenology”, proposed in his Thought Diary (1878-1880), in dialogue both with Husserl’s Contemplative Practice and with Peirce’s version of pragmatism.